Fabrication and evaluation of herbal beads to slow cell ageing - Dhasmana, Archna; Malik, Sumira; Sharma, Amit Kumar; Ranjan, Anuj; Chauhan, Abhishek; Harakeh, Steve; Al-Raddadi, Rajaa M.; Almashjary, Majed N.; Bawazir, Waleed Mohammed S.; Haque, Shafiul (Frontiers in Bioengineering and Biotechnology, 2022)
Several therapies and cosmetics are available commercially to prevent or delay cell ageing, which manifests as premature cell death and skin dullness. Use of herbal products such as Aloe vera, curcumin, vitamin C-enriched natural antioxidant, and anti-inflammatory biomolecules are potential ways to prevent or delay ageing. Eggshell membrane (ESM) is also a rich source of collagen; glycosaminoglycans (GAGs) also play an essential role in healing and preventing ageing. It is important to use an extended therapeutic process to prolong the effectiveness of these products, despite the fact that they all have significant anti-ageing properties and the ability to regenerate healthy cells. Encapsulated herbal components are therefore designed to overcome the challenge of ensuring continued treatment over time to prolong the effects of a bioactive component after in situ administration. To study their synergistic effects on a cellular level, alginate, Aloe vera, and orange peel extract were encapsulated in bio-polymeric foaming beads and modified with eggshell membrane protein (ESMP) at various concentrations (1 gm, 2 gm, and 5 gm): (A-Av-OP, A-Av-OP-ESMP1, ESMP2, and ESMP3). Analysis of the structural and functional properties of foaming beads showed interconnected 3D porous structure, a surface-functionalized group for entrapment of ESMP, and a significant reduction in pore size (51–35 m) and porosity (80%–60%). By performing DPPH assays, HRBC stabilization assays, and antibacterial tests, the beads were assessed as a natural anti-ageing product with sustained release of molecules effective against inflammatory response, oxidative stress, and microbial contamination. MTT assays were conducted using in vitro cell cultures to demonstrate cytocompatibility (in mouse 3T3 fibroblast cells) and cytotoxicity (in human carcinoma HeLa cells). Our study demonstrates that bio-polymeric ESMP beads up to 2 g (A-Av-OP-ESMP2) are practical and feasible natural remedies for suspending defective cell pathways, preventing cell ageing, and promoting healthy cell growth, resulting in a viable and practical natural remedy or therapeutic system.